Pipanisasi Irigasi Dengan Pemanfaatan Energi Non Fosil Pada Lahan Garapan KTH Wonosewu, Mojogedang, Karanganyar - Dwi Priyo Ariyanto; Jaka Suyana; Sumani Sumani; Aktavia Herawati; Komariah Komariah; Jauhari Syamsyiah (Universitas Sebelas Maret, 2024)
Irrigation Pipelining Utilizing Non-Fossil Energy on the Cultivated Land of KTH Wonosewu, Mojogedang, Karanganyar. Forests serve as ecosystems that function as environmental buffers, hosting diverse flora and fauna, with areas covered by stands of hardwood or perennial plants. The cultivated land of the members of KTH Wonosewu Mojogedang, Karanganyar, is located in hilly terrain where irrigation is difficult to obtain during the dry season. This community service activity aims to provide a solution to overcome drought on the cultivated land of the forest farmer group members, with the expectation that avocado cultivation can be carried out effectively and yield good results. This activity is also supported by Forestry Extension Officers who act as intermediaries between the service team and the forest farmer group, thereby harmonizing the implementation of the program. The community service was conducted from March to November 2023 at the Special Purpose Forest Area (KHDTK) Gunung Bromo Karanganyar, Central Java, which serves as the cultivation site for the KTH Wonosewu forest farmer group. The method involved two-way communication between the service team and KTH members to explain the objectives of the activity and to gather feedback or requests from participants related to the program. Subsequently, a pipelining system was developed as a solution to drought, utilizing non-fossil energy through gravity or transmission systems, conveying water through pipes that follow the ups and downs of the land contour. Based on questionnaire data, 100% of the farmer group members responded that the pipelining activity was beneficial, and 86% expressed a desire for continued assistance in managing the irrigation system resulting from this activity.